MAPK-dependent JA and SA signalling in Nicotiana attenuata affects plant growth and fitness during competition with conspecifics - Meldau Stefan; Ullman-Zeunert Lynn; Govind Geetha; Bartram Stefan; Baldwin Ian T (BMC Plant Biology, 2012)
Abstract Background Induced defense responses to herbivores are generally believed to have evolved as cost-saving strategies that defer the fitness costs of defense metabolism until these defenses are needed. The fitness costs of jasmonate (JA)-mediated defenses have been well documented. Those of the early signaling units mediating induced resistance to herbivores have yet to be examined. Early signaling components that mediate herbivore-induced defense responses in Nicotiana attenuata, have been well characterized and here we examine their growth and fitness costs during competition with conspecifics. Two mitogen-activated protein kinases (MAPKs), salicylic acid (SA)-induced protein kinase (SIPK) and wound-induced protein kinase (WIPK) are rapidly activated after perception of herbivory and both kinases regulate herbivory-induced JA levels and JA-mediated defense metabolite accumulations. Since JA-induced defenses result in resource-based trade-offs that compromise plant productivity, we evaluated if silencing SIPK (irSIPK) and WIPK (irWIPK) benefits the growth and fitness of plants competiting with wild type (WT) plants, as has been shown for plants silenced in JA-signaling by the reduction of Lipoxygenase 3 (LOX3) levels. Results As expected, irWIPK and LOX3-silenced plants out-performed their competing WT plants. Surprisingly, irSIPK plants, which have the largest reductions in JA signaling, did not. Phytohormone profiling of leaves revealed that irSIPK plants accumulated higher levels of SA compared to WT. To test the hypothesis that these high levels of SA, and their presumed associated fitness costs of pathogen associated defenses in irSIPK plants had nullified the JA-deficiency-mediated growth benefits in these plants, we genetically reduced SA levels in irSIPK plants. Reducing SA levels partially recovered the biomass and fitness deficits of irSIPK plants. We also evaluated whether the increased fitness of plants with reduced SA or JA levels resulted from increased nitrogen or CO2 assimilation rates, and found no evidence that greater intake of these fitness-limiting resources were responsible. Conclusions Signaling mediated by WIPK, but not SIPK, is associated with large fitness costs in competing N. attenuata plants, demonstrating the contrasting roles that these two MAPKs play in regulating the plants’ growth-defense balance. We discuss the role of SIPK as an important regulator of plant fitness, possibly by modulating SA-JA crosstalk as mediated through ethylene signaling.